Malaria morbidity and mortality in Uganda - Kiwanuka, Gertrude N. (Journal of vector borne diseases, 2003)
Malaria is the leading cause of morbidity and mortality in Uganda especially in children under five years. Transmission of malaria is perennial though there are seasonal exacerbations. Up to 70 per cent of outpatient cases and over 50 per cent of inpatient admissions in the under fives are malaria cases. It is responsible for a specific death rate among this age group of 37/1000 and 18/1000 live births in high and low malaria endemic areas respectively or a total of 70,000–110,000 child health deaths annually. It is also the major killer of refugees and internally displaced people in Uganda. Malaria cases increased from 1,444,352 in 1995 to 2,923,620 in 1999.
Keywords: Child mortality; Malaria morbidity; Miscarriages; Uganda